Studi Awal Resiko Pertambangan Batubara - topo suprihadi (Liaison Journal of Engineering, 2022)
Abstract – Indonesian national energy policy in primary energy supply, targeted contribution of coal in the energy mix by 30% in 2025 which is equivalent to 171.6 x 109 kg of coal and at least 25% equivalent 357 x 109 kg of coal in 2050. Coal mining is a high risk activity for humans, nature and the environment. Therefore, the government program should be escorted by an accurate mitigation scenario. A risk analysis study of coal mining activities have been conducted with the aim of identifying the risk parameters to be taken into consideration in the preparation of adequate mitigation scenario. By using statistical data on coal mining in the United States, has studied a variety of typical coal mining accident, which is dominated by the mine explosion, collapse and subsidence and Suffocation. Coinsidence various causes predictable aggravate accidents. Interference environmental conditions, such as the decline of biodiversity through species extinction, soil and coal dust pollution in the environment, acid mine water pollution, subsidence, erosion, landslides, sedimentation of water bodies will be serious repercussions in mining. Principialy these study are a 'lessons learned; that needs to be sharpened with actual data’s from Indonesia Key Word : Coal, Coal Mine, Surface Mining, Underground Mining, Risk, Accident, Environmental Effects, Disaster, Mitigation.